Supervision of the Pekanbaru City Trade and Industry Service in Distributing Subsidized Cooking Oil - Pratama, Edward; Sadad, Abdul (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Cooking oil is one of the basic needs of Indonesian people in order to fulfill their daily food needs. However, in 2022, Indonesia will experience a shortage of cooking oil stocks, resulting in high cooking oil prices on the market. This phenomenon also occurs in the city of Pekanbaru, so this research aims to determine the supervision of the Pekanbaru City Trade and Industry Department in distributing subsidized cooking oil and find out the obstacles faced in distributing subsidized cooking oil. The theory used is the Supervision theory from Manullang (2015) which uses three indicators, namely establishing a measuring instrument (Standard), carrying out an assessment (Evaluate), and taking corrective action (Corrective Action). The research method used is a qualitative research method. The results of this research conclude that the supervision carried out by the Pekanbaru City Department of Trade and Industry is not optimal, because it is still found that monitoring and evaluation has not been carried out thoroughly and is still limited. The obstacle faced by the Pekanbaru City Trade and Industry Service is the lack of Human Resources (HR) in carrying out supervision, so that the supervision process carried out by the Pekanbaru City Trade and Industry Service cannot cover all areas affected by the price of cooking oil.